Pengaruh Penambahan Virgin Coconut Oil (VCO) Terhadap Sifat Mekanik Dan Biodegradasi Plastik Biodegradable Berbasis Selulosa Bakteri –Polietilen Glikol (PEG) Dari Air Kelapa (Cocos nucifera) - Adhitya Suryadinata; Ananda Putra (Departemen Kimia FMIPA UNP, 2023)
Biodegradable plastics are plastics that are easily degraded by microorganisms. This study aims to determine the effect of adding virgin coconut oil additives to the mechanical properties and biodegradation of biodegradable plastic based on PEG bacterial cellulose from coconut water (Cocos nucifera). This study used 14% polyethene glycol 400 as a plasticizer with variations in the volume of virgin coconut oil, namely 2 mL, 4 mL, 6 mL, and 8 mL. The mechanical properties tested here are looking at the tensile strength, elongation, and elasticity values. The maximum result from testing the mechanical properties obtained is the addition of 6 mL of virgin coconut oil with a tensile strength value of 71,81 MPa which already meets the SNI standard for synthetic plastics, which is in the range of 24,7-302 MPa, the elasticity value obtained is 1819,275 MPa, and 3.9% elongation value. In the biodegradation test, it was found that the 15-day burial was degraded by more than 50%, where the more virgin coconut oil was added, the plastic's biodegradability decreased, but this is still much better than plastic made from synthetic materials, which can take decades. The functional group analysis using FTIR did not show any other functional groups formed, and the results of the analysis of the degree of crystallinity on biodegradable plastics obtained that the degree of crystallinity of pure SB plastic was 83.75%, SBPEG was 70.68%, and SBPEG-V 6 mL 81.31%.